CD15 is a risk predictor and a novel target in clear cell renal cell carcinoma - Stenzel, Philipp J.; Schindeldecker, Mario; Seidmann, Larissa; Herpel, Esther; Hohenfellner, Markus; Hatiboglu, Gencay; Försch, Sebastian; Porubský, Štefan; Macher-Göppinger, Stephan; Roth, Wilfried; Tagscherer, Katrin Elisabeth (Pathobiology, 2024)
Introduction: Tumor cells use adhesion molecules like CD15 or sialylCD15 (sCD15) for metastatic spreading. We analyzed the expression of CD15 and sCD15 in clear cell renal cell carcinoma (ccRCC) regarding prognosis. Methods: A tissue microarray containing tissue specimens of 763 patients with ccRCC was immunohistochemically stained for CD15 and sCD15, their expression quantified using digital image analysis, and the impact on patients’ survival analyzed. The cell lines 769p and 786o were stimulated with CD15 or control antibody in vitro and the effects on pathways activating AP-1 and tumor cell migration were examined. Results: ccRCC showed a broad range of CD15 and sCD15 expression. A high CD15 expression was significantly associated with favorable outcome (p < 0.01) and low-grade tumor differentiation (p < 0.001), whereas sCD15 had no significant prognostic value. Tumors with synchronous distant metastasis had a significantly lower CD15 expression compared to tumors without any (p < 0.001) or with metachronous metastasis (p < 0.01). Tumor cell migration was significantly reduced after CD15 stimulation in vitro, but there were no major effects on the activating pathways of AP-1. Conclusion: CD15, but not sCD15, qualifies as a biomarker for risk stratification and as an interesting novel target in ccRCC. Moreover, the data indicate a contribution of CD15 to metachronous metastasis. Further research is warranted to decipher the intracellular pathways of CD15 signaling in ccRCC in order to characterize the CD15 effects on ccRCC more precisely.